Osmopriming increases jussara palm seed germination - Campos, Thiago Souza [UNESP]; de Souza, Antonio Maricélio Borges; Braga, André Caturelli [UNESP]; Vieira, Guilherme Rodrigues [UNESP]; Pereira, Vânia Maria; Pivetta, Kathia Fernandes Lopes [UNESP] (State University of Mato Grosso do Sul, 2025)
Jussara palm (Euterpe edulis Mart.) is an economically significant palm due to the extraction of the palm heart and acai fruits. However, both extractions reduce the ability of the plant to recover in nature. Thus, it is essential to understand and improve the palm propagation methods. Osmoconditioning is a technology that maximizes seed germination rates and seedling production. In this context, this study aimed to evaluate the effect of different potassium nitrate concentrations on the jussara palm seed germination process. The experiment was set in a completely randomized design. The treatments consisted of five concentrations of KNO3 (0 - control, 1, 2, 3, 4, and 5 g L-1). Four replications were used per treatment, with 25 seeds each. Data collection occurred daily, considering seeds that emitted the coleoptile as germinated until germination stabilized for all treatments. The Germination Speed Index (GSI) was evaluated, and the germination percentage (%) was determined at the end of the experiment. It was found that priming with KNO3 had a significant effect (p<0.05) on all evaluated characteristics. The seeds of the jussara palm showed a linear response with increasing concentrations for germination percentage. Osmoconditioning with KNO3 promotes an increase in the percentage and speed of germination of jussara seeds.
Osmopriming aumenta a germinação de sementes da palmeira juçara
Keywords: Arecaceae; Euterpe edulis Mart; Osmoconditioning; Potassium nitrate